2021
DOI: 10.1007/s00405-021-06622-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhaled fluticasone propionate on laryngotracheal stenosis after balloon dilation: a randomized controlled trial

Abstract: Purpose Laryngotracheal stenosis describes various airflow compromising conditions leading to laryngeal and tracheal narrowing, including subglottic and tracheal stenosis. Direct laryngobronchoscopy is the diagnostic gold standard for laryngotracheal stenosis. This study aimed to explore the effect of inhaled fluticasone propionate as adjuvant medical therapy in patients with laryngotracheal stenosis after balloon dilation. Methods This prospective randomized controlled trial was conducted from April 2019 to A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Some case reports and retrospective series argue for the efficacy of ICS in treating airway stenosis, but there is a paucity of prospective data on the therapy [92,93]. In a small prospective randomized controlled trial (n = 14), the use of ICS in LTS after balloon dilation showed no short-term benefits of treatment [94]. These findings may be explained by a computational analysis using 3-dimensional larynx models that suggests in ideal conditions, only 2.48% of inhaled drug particles may deposit at the site of stenosis [95].…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…Some case reports and retrospective series argue for the efficacy of ICS in treating airway stenosis, but there is a paucity of prospective data on the therapy [92,93]. In a small prospective randomized controlled trial (n = 14), the use of ICS in LTS after balloon dilation showed no short-term benefits of treatment [94]. These findings may be explained by a computational analysis using 3-dimensional larynx models that suggests in ideal conditions, only 2.48% of inhaled drug particles may deposit at the site of stenosis [95].…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…051). More recent studies also found no strong evidence for triple therapy as a whole or for any individual component 6,13,15 . However, these studies were unable to account for therapy compliance.…”
Section: Discussionmentioning
confidence: 93%
“…While there is wide agreement in the theoretical benefit of treating iSGS with ICS and PPI, [12][13][14] the use of TMP-SMX remains the most controversial aspect. 6,15 Since 2005, our institution has regularly prescribed TMP-SMX for iSGS.…”
Section: Triple Therapy Outcomesmentioning
confidence: 99%
“…The delivery modality has varied throughout the years and has been described as systemic, nebulized, delivered through a meter dose inhaler, and submucosal injection. 23 Submucosal injection has been proposed as a delivery modality with minimal side effects due to its limited systemic absorption. 22 The most common agent utilized has been triamcinolone acetonide (40 mg/mL).…”
Section: Choosing Wisely … a Tailored Approach For Challenging Casesmentioning
confidence: 99%